2019
DOI: 10.1021/acs.inorgchem.9b01082
|View full text |Cite
|
Sign up to set email alerts
|

Group 4 Diarylmetallocenes as Bespoke Aryne Precursors for Titanium-Catalyzed [2 + 2 + 2] Cycloaddition of Arynes and Alkynes

Abstract: Despite the ubiquity of reports describing titanium (Ti)-catalyzed [2 + 2 + 2] cyclotrimerization of alkynes, the incorporation of arynes into this potent manifold has never been reported. The in situ generation of arynes often requires fluoride, which instead will react with the highly fluorophilic Ti center, suppressing productive catalysis. Herein, we describe the use of group 4 diarylmetallocenes, Cp R 2 MAr 2 (Cp R = C 5 H 5 , C 5 Me 5 ; M = Ti, Zr), as aryne precursors for the Ticatalyzed synthesis of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…According to the dimensions of the guest and cavity of the host, the o ‐benzyne has space to move inside the host molecule and a static optimized geometry may not be enough to obtain accurate chemical shift values. Note also that the results can be complicated by the fact that o ‐benzyne can react with an aromatic ring of its hemicarcerand host . For this reason, we examined the addition product of a Diels–Alder (DA) reaction between the o ‐benzyne and hemicarcerand 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the dimensions of the guest and cavity of the host, the o ‐benzyne has space to move inside the host molecule and a static optimized geometry may not be enough to obtain accurate chemical shift values. Note also that the results can be complicated by the fact that o ‐benzyne can react with an aromatic ring of its hemicarcerand host . For this reason, we examined the addition product of a Diels–Alder (DA) reaction between the o ‐benzyne and hemicarcerand 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Note also that the resultsc an be complicated by the fact that o-benzyne can react with an aromatic ring of its hemicarcerand host. [45,[57][58][59][60][61] For this reason, we examined the addition product of aD iels-Alder (DA) reaction between the o-benzyne and hemicarcerand 1. o-Benzyne adds to one of the aryl ether units of 1 (diene component) to give the germinal para adduct (see Figure S4 in the Supporting Information). In the 1 HNMR spectrum of the 1@o-benzyne DA adduct, the protons ignals originating from o-benzynew ere identified at 6.14 (H a ), 5.21 (H b ), 4.58 (H c ), and 3.12 ppm (H d ).…”
Section: Incarceration Of O-benzynementioning
confidence: 99%
“…The failure of the bulky or nonterminal alkynes to react with 167′ was postulated as being due to their inability to displace the arene ligand. After this study, the authors concluded that the arene species were involved in the rate-determining step of the [2 + 2 + 2] cyclotrimerization of alkynes.In a recent paper by Reiner and Tonks,230 diarylmetallocenes of type [Cp 2 MAr 2 ] (M = Zr, Ti) 168 were used as aryne precursors for titanium-catalyzed [2 + 2 + 2] cycloaddition of arynes with alkynes (Scheme 67). Only alkynes with bulky substituents afforded naphthalene derivatives in high yields.…”
mentioning
confidence: 85%
“…In a recent paper by Reiner and Tonks, diarylmetallocenes of type [Cp 2 MAr 2 ] (M = Zr, Ti) 168 were used as aryne precursors for titanium-catalyzed [2 + 2 + 2] cycloaddition of arynes with alkynes (Scheme ). Only alkynes with bulky substituents afforded naphthalene derivatives in high yields.…”
Section: [2 + 2 + 2] Cycloaddition Of Three Alkynesmentioning
confidence: 99%
“…In 2019, Tonks and Reiner described the Ti-catalyzed [2+2+2] cycloaddition of arynes and alkynes using Cp* 2 ZrPh 2 to access highly substituted naphthalene derivatives in 86-95% yield (Scheme 19). 79 The reaction was performed in the presence of 1 mol% TiI 4 (THF) 2 with 1-5 mol% Zn 0 in C 6 H 5 Br at 115 °C for 3 h using Cp* 2 ZrPh 2 and the corresponding alkynes. It was demonstrated that bulky Cp* rings were essential to suppress the formation of parasitic metalloindane byproducts (shown in Scheme 19).…”
Section: Scheme 18mentioning
confidence: 99%